2006
DOI: 10.1021/jp061160l
|View full text |Cite
|
Sign up to set email alerts
|

General Method for the Dimension Reduction of Adaptive Control Experiments

Abstract: Adaptive femtosecond control experiments are expanding the possibilities for using laser pulses as photophysical and photochemical reagents. However, because of the large number of variables necessary to perform these experiments (usually 100-200), it has proven difficult to elucidate the underlying control mechanisms from the optimized pulse shapes. If adaptive control is to become a widespread tool for examining chemical dynamics, methods must be developed that reveal latent control mechanisms. This manuscri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 22 publications
(44 reference statements)
0
31
0
1
Order By: Relevance
“…The challenge in understanding the mechanism is tied to the common situation of operating with a large number of control variables and the nonlinearity of the dynamics with respect to the field. In some cases, prior knowledge of the system has permitted expressing the control in terms of a small number of parameters, and principal component analysis [7,8] has found use in seeking a basis set of control variables with reduced dimensionality [9][10][11]. An overall goal is to gain knowledge about the effective complexity of the quantum system expressed in terms of the nature of the participating states under control, which is often not easily deduced from the nominal experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge in understanding the mechanism is tied to the common situation of operating with a large number of control variables and the nonlinearity of the dynamics with respect to the field. In some cases, prior knowledge of the system has permitted expressing the control in terms of a small number of parameters, and principal component analysis [7,8] has found use in seeking a basis set of control variables with reduced dimensionality [9][10][11]. An overall goal is to gain knowledge about the effective complexity of the quantum system expressed in terms of the nature of the participating states under control, which is often not easily deduced from the nominal experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…For unshaped pulse experiments [30 fs FWHM via autocorrelation; near transform limited (TL)] a constant phase was sent to the shaper, while for pulse shaping experiments a threeparameter phase function was used (see below). The adaptive algorithm uses evolutionary strategies described in detail elsewhere [15]. A portion of the absorption spectrum of the film used, is shown in Fig.…”
mentioning
confidence: 99%
“…Using the probe spectrum for feedback, a i , b i , and c i were optimized using an evolutionary algorithm to find the best coefficients for the desired outcome [12]. This basis set was chosen to approximate the pulse shapes that Meier and Heitz predicted would optimize the vibrational excitation of the metal carbonyl in carboxyhemoglobin [9] while simultaneously limiting the dimensions of the control space [13]. We found that four sine waves were the fewest necessary to achieve the desired optimization.…”
mentioning
confidence: 99%